Education for Medical Personnel Malpractice: A Literature Review - Kadek Ayu Putri Dharma Putra; Sagung Putri ME Purwani; Devi Fitriyastanti; Silvia Anitasari (Jurnal Penelitian Pendidikan IPA, 2023)
Doctors who adhere to professional standards, service standards, and standard operating procedures can generally expect legal protection in their medical practice. Following established protocols and guidelines helps ensure that doctors provide care within accepted norms, reducing the likelihood of malpractice allegations. This is a literature review study that analyzed the literature related to the malpractice law. The initial involved searching various databases, including MEDLINE via PubMed, Scopus, and Web of Science from April to May,2023. This search was performed using specific terms, namely doctor, dentist, malpractice, and Indonesian laws. The literature search yielded a total 153 citation (Fig. 1). Upon completion of title and abstract screening, 75 full-texts were deemed potentially relevant and reviewed. Subsequently, 21 documents fulfilled our eligibility criteria and were included. The Medical Council of Indonesia (MKDKI) has the authority to examine complaints related to the discipline of doctors and dentists and determine whether any mistakes were made in the application of medical and dental disciplines. The decisions made by MKDKI can have implications for the professional standing and disciplinary actions against doctors.